Procesy kształtowania się przemysłu komputerowego Brazylii - Mirosław Wójtowicz (Prace Komisji Geografii Przemysłu Polskiego Towarzystwa Geograficznego, 2009)
The article examines development of the Brazilian industrial policy in the IT sector from the creation in 1959 a special agency concerned with computers – the Grupo Executivo para Aplicação de Copmputadores Electrônicos (GEACE) to the liberalization of the informatics policy introduced in 1991 and Computador para Todos program introduced in 2003. The IT policies prevailing in the 1970s and 1980s were oriented toward national production and development of technological capabilities. Since the 1991 protectionism was replaced by liberal policy with incentives and tax rebates as alternative mechanisms preserving some local equipment manufacturing and R&D activities. The general economic success after the introduction in the 1994 Real Plan was also visible in the computer industry. During the years 1994–2006 the employment in this industry has more than tripled and the production of computers increased substantially.